Lärdomar från utveckling av inflekterande synonymordböcker - Arppe, Antti (Nordiske Studier i Leksikografi, 2001)
During 1996-1998, product development projects were carried out at Lingsoft in order to create so-called inflecting thesauri, in which the electronic form of the contents of synonym dictionaries for Swedish, Danish, and Norwegian Bokmål were integrated with computerized morphological models, created according to the two-level mode!, for the respective languages. The resultant computer programs provided practical insights into the interaction between structures of semantic relations, in this case representing synonymity, and with inflectional morphology. As a result, it became evident that the principle of lexical generality cannot be trusted blindly in generating across the board the inflected forms of the base-form components of a synonym dictionary. Furthermore, it would seem that synonymity between words cannot be categorically expected to extend throughout the entire inflectional paradigm of these words. This would suggest that inflected forms of words should also be considered when constructing structures of semantic relations.